Confronting the “Green” Discourse of Librarianship - Kirby, Michael (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2026)
Set against the backdrop of resurgent right-wing populism and drawing on Sam Popowich’s critique of democratic discourse in librarianship, this article outlines a crisis of imagination within liberal climate activism—particularly its essentially unquestioned commitment to “green growth,” or the notion that economic expansion can continue indefinitely alongside ecological sustainability. The American Library Association (ALA), despite its progressive public image, uncritically promotes these same market-oriented solutions to climate change and aligns itself with international treaties such as the Kyoto Protocol and the Paris Agreement, both of which are grounded in growth-centric frameworks and market mechanisms like carbon credits. These frameworks and mechanisms, the article finds, function as forms of greenwashing—symbolic gestures that allow corporations and institutions to appear environmentally responsible while continuing to push unsustainable practices.